THE UTILIZATION OF WOODEN TWIG WASTE TO BE A CRAFTS PRODUCT AS A BUSINESS OPPORTUNITY IN THE PANDEMIC TIME OF COVID-19 - Eka Mutia; Meilandy Purwandito; Ellida Novita Lydia (LPPM dan PM Universitas Samudra, 2021)
Wood twig waste comes from felling trees or from fallen trees. The only part of the tree that can be used is the trunk of wood, while the wood branches that have a large amount cannot be used. The waste that nags at the wood will be burned so that it will pollute the air for the surrounding environment. Waste wood twigs can be used into handicraft products that have a higher economic value by using the lamination technique. Lamination technique is to join small pieces of wood to form an object or plane with a strong adhesive. With this technique, tree branches that have been used as waste can be turned into handicraft products such as serving mats, photo frames, tissue holders and other containers. Utilization of wood waste into handicraft products can open business opportunities for the community. The covid 19 virus pandemic has caused many people to lose their jobs and wood waste management can be one of the community's creative efforts. The resulting handicraft products can be marketed online so that people can still work at home and have their own businesses.